Peranan Nelson Mandela dalam Memperjuangkan Demokrasi di Afrika Selatan Tahun 1990-1994 - Futri Rahayu Gusmiarni; Murdiyah Winarti; Ayi Budi Santosa (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
This study aims to 1) describe the reasons and process for the change of President Pieter Willem Botha to Frederik Willem de Klerk, 2) describe the various struggles that Nelson Mandela has made to realize democracy in South Africa in 1990-1994, 3) describe the results of the efforts that have been made. carried out by Nelson Mandela realizing democracy in 1994. The research method used to examine this research is the historical method by carrying out 4 stages including heuristics, source criticism, interpretation, and historiography using literature study as a research technique. The findings of this study can be opened that first, in 1990 the government led by Pieter Willem Botha had begun to revive the condition, which was clouded by the many incidents carried out by black people who attracted international attention, because of the pressure that was obtained and then founded, Frederik Willem de Klerk. President Frederik Willem de Klerk made demands for blacks to attend Nelson Mandela and other politics and abolish apartheid's political laws. Second, after being released from prison, Nelson Mandela was again active in politics with the ANC in his struggle this time he had to deal with his own group, the dispute between the ANC and Inkatha that claimed lives and at the same time had to carry out his mission to gather support for the ANC. The government led by Frederik Willem de Klerk finally agreed to hold the first general election in South Africa which was held on 27 April 1994. Third, the election was won by the ANC party by obtaining 252 votes, Nelson Mandela was then black President in South Africa for the period 1994- 1999.Keywords: apartheid politics, democracy, nelson mandela